Impact of microcredit programmes on participants' behaviour in Malaysia: an overview / Zuraidah Mohamed Isa ... [et al.] - Mohamed Isa, Zuraidah; Ibrahim, Dahlia; Ahmad Zabib, Zaiful Affendi (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The idea of microcredit is not new. It was introduced in the 1970s by Professor Muhammad Yunus, who was actively involved in poverty alleviation programmes. In 1976, he visited very poor households in the village of Jobra. He used his own money to provide financial assistance to 42 poor individuals. Satisfied with the repayment of these loans, he was prompted to expand the financial assistance using a more structured banking system. Subsequently, Grameen Bank was established in 1983. Inspired by Grameen Bank's achievement, the approach of giving away loans to poor people was adopted in Malaysia, starting with the initiation of a pioneer project in the north-western area of Selangor, known as Project Ikhtiar. Project Ikhtiar is deemed to be successfully implemented, and the success of the project proves that the microcredit project is helpful in improving the quality of life of the poor. This initial success led to the birth of Amanah Ikhtiar Malaysia (AIM) on 17th September, which is aimed to reduce poverty among the poor and hardcore poor households in Malaysia.